ANALYZING THE RELATIONSHIP BETWEEN TYPES OF ADVERTISEMENT AND CUSTOMER CHOICE : A STUDY OF RETAILER STORES IN ERBIL - Anwar, Kofand; Climis, Raghda (The International Journal of Accounting and Business Society, 2017)
In today’s competitive business environment advertisement and constant promotion techniques are being frequently used to motivate purchasers and attract them to purchase a particular product. The study aimed to examine the relationship between types of advertisement with consumer purchasing choice in retailer stores in Erbil. The researchers gathered data through questionnaires from randomly selected customers; however 268 purchasers were involved in the current study. The findings revealed that the highest value was for online advertisement has the strongest relationship with consumer purchasing choice in retailer stores in Erbil, on the other hand outdoor advertisement has the weakest relationship with consumer purchasing choice in selecting certain retailer store in Erbil. Retailer stores should to keep up with market development to enable attracts customers. The marketplace is currently in the internet generation which indicates that retailer stores should invest more efforts and time in creating effective social media connections and provide online shopping to the customer to get closer.